Neural processes for live pro-social dialogue between dyads with socioeconomic disparity. Issue 8 (3rd September 2020) - Descorbeth, Olivia; Zhang, Xian; Noah, J Adam; Hirsch, Joy
Abstract: An emerging theoretical framework suggests that neural functions associated with stereotyping and prejudice are associated with frontal lobe networks. Using a novel neuroimaging technique, functional near-infrared spectroscopy (fNIRS), during a face-to-face live communication paradigm, we explore an extension of this model to include live dynamic interactions. Neural activations were compared for dyads of similar and dissimilar socioeconomic backgrounds. The socioeconomic status of each participant was based on education and income levels. Both groups of dyads engaged in pro-social dialectic discourse during acquisition of hemodynamic signals. Post-scan questionnaires confirmed increased anxiety and effort for high-disparity dyads. Consistent with the frontal lobe hypothesis, left dorsolateral pre-frontal cortex (DLPFC), frontopolar area and pars triangularis were more active during speech dialogue in high than in low-disparity groups. Further, frontal lobe signals were more synchronous across brains for high- than low-disparity dyads. Convergence of these behavioral, neuroimaging and neural coupling findings associate left frontal lobe processes with natural pro-social dialogue under 'out-group' conditions and advance both theoretical and technical approaches for further investigation.